Curriculum development in language teaching - Richards, Jack C. (Cambridge University Press, 2017)
Agendas for Second Language Literacy by Sandra Lee McKay Reflective Teaching in Second Language Classroomsby Jack C. Richards and Charles Lockhart Educating Second Language Children: The whole child, the whole curriculum, the whole community edited by Fred Genesee Understanding Communication in Second Language Classrooms by Karen E. Johnson The Self-directed Teacher: Managing the learning process by David Nunan and Clarice Lamb Functional English Grammar: An introduction for second language teachers by Graham Lock Teachers as Course Developersedited by Kathleen Graves Classroom-based Evaluation in Second Language Education by Fred Genesee and John A. Upshur From Reader to Reading Teacher: Issues and strategies for second language classrooms by Jo Ann Aebersold and Mary Lee Field Extensive Reading in the Second Language Classroomby Richard R. Day and Julian Bamford Language Teaching Awareness: A guide to exploring beliefs and practices by Jerry G. Gebhard and Robert Oprandy Vocabulary in Language Teaching by Norbert Schmitt Curriculum Development in Language Teaching by Jack C. Richards